Crystal structure, electrochemistry, and catalytic studies of a series of new oxidovanadium(IV) Schiff-base complexes derived from 1,2-diphenyl-1,2-ethylenediamine - Ghaffari, Abolfazl; Behzad, Mahdi; Dutkiewicz, Grzegorz; Kubicki, Maciej; Salehi, Mehdi (Journal of coordination chemistry, 2012)
New derivatives of N 2 O 2 tetradentate Schiff bases, from condensation of meso-1,2-diphenyl-1,2-ethylenediamine and salicylaldehyde derivatives (X-salicylaldehyde; X = 3-OMe, 4-OMe, 5-OMe, 6-OMe, 5-Cl, 5-Me), and oxidovanadium(IV) complexes were synthesized and characterized by 1 H NMR, UV-Vis, IR spectroscopy, and elemental analysis. Crystal structure of 5-OMe; H 2 L 3 and two of the complexes (VOL 2 and VOL 3 ) were also obtained. In the crystals, the molecule of H 2 L 3 is C i symmetrical, as it occupies the special position on the center of symmetry; its conformation is partially determined by classical intramolecular O-H···N hydrogen bonds. The complexes have monomeric structures with a distorted square pyramid of vanadium, with the oxo ligand in the apical position. Cyclic voltammetry studies show quasi-reversible V IV /V V redox for which the presence of electron-withdrawing groups on salicylaldehyde derivatives shifts the E° to more positive values. The complexes were used as catalysts for selective epoxidation of cyclooctene with tert-butylhydroperoxide as oxidant, in various solvents and reaction conditions. High catalytic activities and excellent selectivity was found. The catalytic activity of the complexes increased increasing E°, a consequence of the presence of electronegative substituents. This epoxidation process with the new catalysts was also studied under solvent-free condition and excellent reactivity was observed.